PENGARUH LITERASI KEUANGAN TEKNOLOGI DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA KEUANGAN UMKM DIMEDIASI KEUNGGULAN BERSAING - Ana Tasya Fitriani; Wida Purwidianti (Politeknik Ganesha Medan, 2026)
This study investigates the effects of financial literacy, technology adoption, and entrepreneurial orientation on the financial performance of Micro, Small, and Medium Enterprises (MSMEs), while also examining the mediating role of competitive advantage in the Purwokerto area. A quantitative research design with an associative approach was employed to explore the relationships among the proposed variables. The study involved 120 MSME owners selected through purposive sampling based on specific eligibility criteria. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), which enabled the assessment of both the direct effects among variables and the indirect effects through competitive advantage. The analysis reveals that financial literacy, technology adoption, and entrepreneurial orientation each contribute positively and significantly to the development of competitive advantage as well as to the improvement of MSMEs' financial performance. In addition, competitive advantage demonstrates a significant positive effect on financial performance. The findings further indicate that competitive advantage serves as an effective mediating variable, strengthening the influence of financial literacy, technology adoption, and entrepreneurial orientation on financial outcomes. These results emphasize that improving financial knowledge, encouraging the effective utilization of digital technology, and cultivating a strong entrepreneurial mindset are essential strategies for enhancing the competitiveness and financial sustainability of MSMEs in Purwokerto. The study also provides practical insights for business owners and policymakers by highlighting the importance of integrating managerial competencies with sustainable competitive strategies to achieve better financial performance in an increasingly dynamic and digital business environment.